Science Feminis: Sebuah Kajian Sosiologi Pengetahuan - Aris Soleman; Reza Adeputra Tohis (SPECTRUM: Journal of Gender and Children Studies, 2021)
Feminism science is a science that makes women both the subject and the object of research. This study aims to reveal the social processes of the formation of feminism science. This research uses qualitative research methods with scientific theory study techniques, and uses the sociology of knowledge as an analytical approach. The result of this research is that the social process of the formation of feminism science takes place in three momentums, namely, externalization and objectification in which feminist movements and thoughts emerge in three phases which provide the foundation for the formation of feminism science in its internalization momentum. Abstrak Science feminis adalah ilmu pengetahuan yang menjadikan perempuan sebagai subjek sekaligus objek penelitian. Penelitian ini bertujuan mengungkap proses-proses sosial terbentuknya science feminisme . Penelitian ini menggunakan metode penelitian kualitatif dengan teknik studi teori ilmiah, dan menggunakan sosiologi pengetahuan sebagai pendekatan analisis. Hasil dari penelitian ini adalah bahwa proses sosial terbentuknya science feminis berlangsung dalam tiga momentum yakni, eksternalisasi serta objektifikasi di mana gerakan dan pemikiran feminis muncul dalam tiga fase yang memberikan landasan bagi terbentuknya science feminis dalam moemntum internalisasinya. Penelitian ini juga menunjukan wacana sains feminis di Indonesia.